STUDI KUANTITATIF KINERJA PENGELOLAAN PIUTANG PBB-P2 KOTA YOGYAKARTA DAN KOTA PARIWISATA LAINNYA - gupita candra; Ambarwati, Lilik (Universitas Sarjanawiyata Tamansiswa, 2025)
Accumulation of tax receivables presents an ongoing challenge for revenue management authorities. Therefore, efficient tax receivable management at a manageable level is a crucial factor in improving local government performance and optimizing regional tax revenue. This study aims to determine the performance of PBB-P2 receivable management in Yogyakarta City and compare it with other tourist cities from 2021 to 2023. The data were obtained from public information disclosures and the financial accountability reports of the Regional Budget (APBD) from Yogyakarta City, Bandung City, Malang City, and Denpasar City. The study employs a quantitative descriptive analysis method. The findings reveal that Yogyakarta City has the highest PBB-P2 revenue ratio per square kilometer and ranks first in PBB-P2 receivable management performance, with an average ratio of receivable growth to current-year PBB-P2 revenue of 12.07%. This indicates that efforts to increase tax revenue have been significantly greater than the accumulation of receivables. Bandung City, Malang City, and Denpasar City follow with respective ratios of 13.87%, 22.37%, and 25.7%. Despite Yogyakarta City demonstrating the highest performance, the declining trend from 2021 to 2023 underscores the need for further evaluation by the Regional Financial and Asset Management Agency (BPKAD) of Yogyakarta City to enhance the efficiency of tax receivable management.